Pengaruh debt to equity ratio (der) dan return on equity (roe) terhadap harga saham perusahaan manufaktur sektor aneka industri di Indonesia - Muhammad Rezi Sudimas; Riyanto Wujarso (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
This study aims to examine the effect of Debt to Equity Ratio (DER) and Return on Equity (ROE) on stock prices. The independent variables used in this study are DER and ROE. Meanwhile, the dependent variable in this study is stock prices. The population in this study is in the form of annual financial report data from 52 companies in miscellaneous industry sectors for the period 2016-2019. Determination of the research sample using purposive sampling and obtained a sample of 15 companies. The results showed that the DER t test did not have a significant effect on stock prices, this is evidenced by the DER significance value of 0.147, 0.147 > 0.05. While ROE has a significant effect on stock prices, this is evidenced by the ROE significance value of 0.000, 0.000 < 0.05. In the results of the F test, DER and ROE have a simultaneous and significant effect on prices, this is evidenced by the calculated F value of 213.560, the value of 5.749 > 3.16. The significance value of 0.000, the value of 0.000 > 0.05, means that there is an influence between DER and ROE simultaneously on stock prices. It means that there is an influence between DER and ROE simultaneously on the stock price of 88%, while the remaining 12% is the influence of other factors not examined. This is evidenced by the r square value (r2) of 0.882